Funding State Courts:Trends in 2002: Budget Woes and Resourceful Thinking - (:unkn) unknown (My University, 2016)
That most courts are sharing in the pains caused by the current recession is hardly news. That circumstances are likely to worsen before they improve is also widely accepted. Nevertheless, if historic patterns hold, the courts will fare better than most executive branch agencies during the short term; as institutions, the courts are in no immediate danger. Less certain is how courts will position themselves during this period of austerity and how their actions, and developments in other areas, will affect the long-term quality of justice.